Optimization of peppermint (Mentha piperita L.) extraction using solvent-free microwave green technology - Delita Kunhermanti; Mahfud Mahfud (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Peppermint varieties indigenous to Europe and the Middle East are now widely cultivated in various regions, such as Indonesia. Peppermint is the main species of natural raw material in producing peppermint essential oil for its applications in the pharmaceutical, perfumery, and food flavour industries. The main challenge of extracting essential oil lies in optimizing different efficient and sustainable techniques for that proposed conventional extraction, which is usually based on high temperatures for a long time. Alternative green extraction techniques have emerged, such as those based on microwave-assisted extraction. In this study, solvent-free microwave extraction (SFME) has been applied to extract essential oil from Mentha piperita Linn, and response surface methodology (RSM) was selected to evaluate extraction conditions. The optimized variable parameter was microwave power (150-450 Watt), feed-to-distiller volume (F/D) ratio (0.08-0.12 g/mL), and particle size (0.5-1.5 cm). The optimum yield obtained was 0.6937% under operational conditions with 450 Watts of microwave power, 0.1 g/mL of F/D ratio, 1cm of particle size, and an extraction time of 60 minutes.